Ekperimentasi Model Pembelajaran Discovery dan Group Investigation Terhadap Prestasi Belajar Matematika Ditinjau dari Kreativitas Siswa - Vahlia, Ira (AKSIOMA (Jurnal Pendidikan Matematika), 2014)
The aim of the research was to determine the effect ofÂ  learning models on mathematics achievement viewed from the student creativity. The learning model compared were discovery, group investigation and conventional. The type of the research was a quasi-experimental research. The population was the students of Junior High Schoolin Surakarta city on academic year 2012/2013. The samples of this research were taken by using the stratified cluster random sampling technique. The samples consist of 281 students who were divided into 94 students in the first experiment class, 94 students in the second experiment class, and 93 students in the control class. The results of this research are as follows: (1) the discovery learning model results in better learning achievement than the group investigation and conventional learning model. The group investigation learning model results in an equal learning achievement to the conventional learning model, (2) the students having high level of creativity have better learning achievement than those having medium and low levels of creativity. The students having medium level of creativity have an equal learning achievement to those having low level of creativity, (3) on the discovery learning model, students having high creativity have better learning achievement than those having medium and low levels of creativity and students having medium level of creativity have an equal learning achievement to those having low creativity. On the group investigation model, students in each level of creativity have the same learning achievement, (4) the students who were tought with the discovery learning model have better learning achievement than those taught with the group investigation and conventional learning model in the category of having high level of creativity. The students who were tought group investigation and conventional model results in an equal learning achievement in the category of having high level of creativity. The students having medium level of creativity have an equal learning achievement to those having low level of creativity in each learning model.